Nurses performance and bioethical concepts through the donation of organs and tissues (Research, Society and Development, 2022)
The purpose of the study is to comprehend using a bibliographic review study, the role of nurses during the process of organ and tissues donations, and the bioethical precepts related to it. This is a bibliographic review study with a qualitative approach. The article was carried out by researching documents through the Medical Subject Headings (MeSH): “Tissue and Organ Procurement”, “Brain Death”, “Nursing Care”, “Bioethics”. The search was performed between April and May 2022 in the following databases: Virtual Health Library (VHL), Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library (SciELO), Ministry of Health of Brazil and on the Brazilian Federal Council of Medicine and Nursing. Thus, 15 documents relevant to the study were selected. Its possible to recognize that the nurse has an important role during this process, working in the elaboration and potentiation of all the process of the tissue and organ donation, given that they collaborate with the diagnosis of brain death, in the retrieval, in addition to assisting the family during the grief process and in the decision making, since during the procedure to the recovery period. Furthermore, it was found that it is extremely important to respect bioethical principles from the death of the patient who donates to the reception of the organ by the recipient patient.